2011
DOI: 10.3233/jad-2010-101335
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Amyloid-β as a Function of Age, Level of Intellectual Disability, and Presence of Dementia in Down Syndrome

Abstract: Adults with Down syndrome (DS) are at risk for developing Alzheimer disease (AD). While plasma Aβ is known to be elevated in DS, its relationship to cognitive functioning is unknown. To assess this relationship, samples from two groups of subjects were used. In the first group, nondemented adults with DS were compared to: 1) a group of young and old individuals without DS and 2) to a group of patients with AD. Compared to these controls, there were significantly higher levels of plasma Aβ in nondemented adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
85
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 66 publications
(92 citation statements)
references
References 52 publications
6
85
1
Order By: Relevance
“…In one study, the results of the cognitive assessments were available only as supplemental data [46]. Three other studies reported no objective data from cognitive assessments [39,41,42]. In another 3 studies, it was necessary to refer to earlier studies by the same group in order to determine which cognitive assessment instruments were used [39,42,43].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In one study, the results of the cognitive assessments were available only as supplemental data [46]. Three other studies reported no objective data from cognitive assessments [39,41,42]. In another 3 studies, it was necessary to refer to earlier studies by the same group in order to determine which cognitive assessment instruments were used [39,42,43].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 14 studies, only 2 focused on the cognitive assessment of individuals with DS and AD [20,36]. There were 11 studies in which the main focus was AD in DS [12,20,35,36,37,38,39,40,41,42,43]; there was 1 study in which the central theme was functional aspects of AD in adults with intellectual disability [44], and there were 2 studies that focused on aging individuals with DS but not necessarily on aspects related to dementia [45,46]. Of the 11 studies focusing on AD in DS, 2 included only subjects diagnosed with DS and AD [12,37], whereas the others involved control groups of individuals without AD, without DS, or even without intellectual disabilities.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations